From diagnosis to complications: experiences of those who live with systemic lupus erythematosus - Rebeca Rosa de Souza; Sonia Silva Marcon; Elen Ferraz Teston; Mayckel da Silva Barreto; Pamela dos Reis; Hellen Pollyanna Mantelo Cecilio; Verônica Francisqueti Marquete; Patricia Chatalov Ferreira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To understand how people with lupus experience the diagnosis and how they deal with complications arising from the disease. Method: Qualitative study, whose data were collected between February and July 2019, through semi-structured interviews with 26 individuals and submitted to content analysis. Results: Three categories emerged that show illness from lupus as a difficult experience, permeated by sadness, fear and suffering, which, in addition to being linked to society's lack of knowledge about the disease, negatively impacts the lives of those who experience it. Furthermore, they show that the time of living with the disease favors the development of self-care strategies and greater therapeutic adherence and, consequently, longer periods of disease remission. Considerations: More disclosure about the disease and its implications in the daily lives of those affected is essential, culminating in greater understanding of family, friends and colleagues and improvements in health care and quality of life for these people.